A novel biosorbent prepared by immobilized Bacillus licheniformis for lead removal from wastewater. (June 2018) - Wen, Xiaofeng; Du, Chunyan; Zeng, Guangming; Huang, Danlian; Zhang, Jinfan; Yin, Lingshi; Tan, Shiyang; Huang, Lu; Chen, Hong; Yu, Guanlong; Hu, Xuyue; Lai, Cui; et al.
Abstract: Magnetic polyving akohol (PVA) immobilized the endogenous bacterium Bacillus licheniformis with sodium alginate to get a novel biosorbent. The optimum preparation and adsorption conditions were studied. The optimal preparation conditions was the fraction of magnetic PVA was 9%, the fraction of sodium alginate was 0.8%, the fraction of microbial suspensions was 5% and the crosslinking time was 20 h. The best adsorption conditions were listed as follows: pH was 6, the biosorbent dosage was 0.7 g L −1, the initial concentration of lead ions was 200 mg L −1 and the optimal adsorption time was 12 h. The results of SEM and FTIR spectroscopy analysis displayed this novel biosorbents had good structure and the functional groups on the surface was abundant. The VSM analysis confirmed the novel biosorbents had good magnetic magnetization and were easily separated from aqueous medium. Under the optimum conditions, the removal rate of lead ions from waste water could reach 98%, the calculated maximum adsorption capacity could be up to 113.84 mg g −1 . The whole adsorption process was well fit by the pseudo-second order kinetic and it was also a Langmuir monolayer adsorption. The desorption experiments showed the biosorbent had good re-usability. Highlights: A novel biosorbent: magnetic polyvinyl alcohol immobilized the entophytic bacteria Bacillus licheniformis was prepared. Optimum prepared conditions were explored as the fraction of magnetic polyvinyl alcohol, the crosslinking time, etc. Optimum biosorption conditions were studied as the pH of solution, the adsorbent dosage, etc. Pseudo-second-order and Langmuir models best described the lead ions adsorption. The biosorbents had large capacity for lead ions removal, high separability from solutions and good re-usability.